2004
DOI: 10.1111/j.1365-2745.2004.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic interactions between competition and insect herbivory on plant growth

Abstract: Summary1 Although substantial theoretical work suggests that competition and herbivory should exhibit a wide variety of interactions in their effects on plant growth, empirical studies have shown that the predominant interactions are simply multiplicative. 2 To determine both the relative strengths of, and interactions between, competition and herbivory, we conducted a field experimental study in a native grassland using four focal species: Koeleria macrantha , Coreopsis tinctoria , Linum lewisii and Helianthu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 62 publications
(93 reference statements)
3
60
2
Order By: Relevance
“…Then, the shoot and root biomass reduction for the soil feedback effect (difference between own and control soil) and the effect of herbivore reduction (difference between herbivory and no-herbivory treatment) were calculated for each plant species, added, and compared with the treatment where plants were exposed to the combination of soil feedback and aboveground herbivory ( Fig. 2; Haag et al 2004). Because plant biomass data are always positive they tend to follow a logarithmic distribution when biomass values approach zero, which would transform the linear additive effect towards a multiplicative effect (Slob 1987).…”
Section: Methodsmentioning
confidence: 99%
“…Then, the shoot and root biomass reduction for the soil feedback effect (difference between own and control soil) and the effect of herbivore reduction (difference between herbivory and no-herbivory treatment) were calculated for each plant species, added, and compared with the treatment where plants were exposed to the combination of soil feedback and aboveground herbivory ( Fig. 2; Haag et al 2004). Because plant biomass data are always positive they tend to follow a logarithmic distribution when biomass values approach zero, which would transform the linear additive effect towards a multiplicative effect (Slob 1987).…”
Section: Methodsmentioning
confidence: 99%
“…Third, the insecticide treatment, by being concentrated only on the focal experimental plant rather than on the entire plot, could have increased herbivory on the neighbor plants by shared generalist herbivores, weakening the competitive effect on the focal rosette (Haag et al 2004). We did not measure herbivory on the neighboring plants in our plots; however, we found that neighboring plants did not reduce herbivory on the focal plant (Table 1), suggesting neighbors did not lure herbivores off of our focal experimental plant.…”
Section: Interaction Of Competition and Herbivorymentioning
confidence: 99%
“…If the effects of herbivory and competition are antagonistic, then their joint effect on plant performance should be less than the product of their individual effects. Antagonistic interactions could result if neighbors hide a plant from its herbivores, reducing the magnitude of herbivory (also known as associational resistance) (Tahvanainen and Root 1972); or, it could result if herbivores feed preferentially on the neighbor plants reducing their competitive effect on the focal plant (Hamilton et al 1998;Haag et al 2004). Since competition and herbivory are widespread, understanding whether and how they interact to limit plant reproduction is of general importance in predicting population dynamics in basic and applied contexts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our finding that effects of aboveground parts of neighbor plants and insect folivory acted independently in reducing growth of tall thistle rosettes adds to a short but growing list of field experiments in natural or agroecosystems that demonstrate that independent effects of neighbor plants and insect folivory on host plant growth may be more common than either synergistic or antagonistic interactions (independent effects on growth: Rees and Brown 1992, McEvoy et al 1993, Erneberg 1999, Newingham and Callaway 2006; synergistic effects on growth: Nötzold et al 1998, Agrawal 2004; antagonistic effects on growth: Haag et al 2004). In spite of the independence of their effects on plant growth, we did find evidence that the presence of neighbor plants magnified the impact of insect folivory on the transition rate of rosettes to reproductive life-stages.…”
Section: Combined Effects Of Neighbor Plants and Insect Folivorymentioning
confidence: 60%